Study on the growth characteristics of Pinus yunnanensis seedlings based on hormonal regulation and chlorophyll metabolism - Ruilian Li; Qibo Wang; Sunling Li; Lin Chen; Nianhui Cai; Yulan Xu (Scientific Reports)
Abstract Pinus yunnanensis is an important coniferous species for both ecological and economic purposes in Southwest China. However, its seedlings grow slowly and show low productivity, with notable trait variability under the same cultivation conditions. These characteristics limit its extensive use in reforestation and forest management. Photosynthesis is the foundational process for plant growth and biomass accumulation. Chlorophyll, as the essential pigment in photosynthesis, directly impacts the synthesis of organic materials and the increase in biomass. In this study, the seedlings of P. yunnanensis were classified into three grades (I, II, and III) using the mean value ± 1/2 standard deviation method (H ± 1/2σ). Various growth traits, such as the number of branches, plant height, stem thickness, needle length, root characteristics, and biomass, were measured at multiple time points. The content of photosynthetic pigments was determined using spectrophotometry, endogenous hormone levels were analyzed by LC-MS/MS, and the expression of genes related to chlorophyll metabolism was detected through qRT-PCR. Pearson correlation analysis was employed to quantify the associations between hormone content, gene expression, and the seedlings’ morphological characteristics. The results indicate that Grade I significantly outperform Grades II and III in terms of above-ground growth metrics. During the rapid growth period in March, Grade I seedlings had the highest chlorophyll content, potentially enhancing photosynthetic efficiency and increasing biomass allocation. Hormonal analysis revealed that compared to other grades, Grade I seedlings exhibited higher levels of ABA, JAs, and ACC, while Auxins and SAs were lower; there was no significant difference in CTK content between Grade I and Grade II, both of which were lower than in Grade III. qRT-PCR analysis confirmed that the expression of genes related to chlorophyll synthesis was significantly upregulated in Grade I seedlings. In contrast, the expression of genes associated with chlorophyll degradation was more active in Grade III seedlings. Correlation analysis further emphasized the strong link between hormone levels, gene expression, and growth traits. This study delves into the intrinsic mechanisms of morphological differentiation in P. yunnanensis seedlings by examining the synergistic effects of chlorophyll metabolism and endogenous hormone regulation. These findings can provide valuable references for cultivating high-quality seedlings, optimizing seed source selection, and improving afforestation techniques.